2021
DOI: 10.3390/ijms22179193
|View full text |Cite
|
Sign up to set email alerts
|

Compromised Biomechanical Properties, Cell–Cell Adhesion and Nanotubes Communication in Cardiac Fibroblasts Carrying the Lamin A/C D192G Mutation

Abstract: Clinical effects induced by arrhythmogenic cardiomyopathy (ACM) originate from a large spectrum of genetic variations, including the missense mutation of the lamin A/C gene (LMNA), LMNA D192G. The aim of our study was to investigate the biophysical and biomechanical impact of the LMNA D192G mutation on neonatal rat ventricular fibroblasts (NRVF). The main findings in mutated NRVFs were: (i) cytoskeleton disorganization (actin and intermediate filaments); (ii) decreased elasticity of NRVFs; (iii) altered cell–c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…In a 2021 study, a pulsed optical tweezer was used to detect the viscosity parameters of wild-type and A350P lamin A, and it was found that the complex viscosity for A350P lamin A was higher than that of wild-type lamin A, which may translate into nuclear plasticity ( Mukherjee et al, 2021 ). Moreover, mutation of the lamin A/C gene D192G also led to weakened tunneling nanotubes (TNTs) and compromised cell–cell adhesion in neonatal rat ventricular fibroblasts, as shown by biomechanical studies using optical tweezers ( Lachaize et al, 2021 ). To date, the topic of lamin mechanics is still vastly unstudied, and this application of optical tweezers could definitely be extended to examine the mechanics of other mutant lamins, as well as any other intermediate filaments.…”
Section: Single-molecule Studies Of Cardiovascular Diseasesmentioning
confidence: 99%
“…In a 2021 study, a pulsed optical tweezer was used to detect the viscosity parameters of wild-type and A350P lamin A, and it was found that the complex viscosity for A350P lamin A was higher than that of wild-type lamin A, which may translate into nuclear plasticity ( Mukherjee et al, 2021 ). Moreover, mutation of the lamin A/C gene D192G also led to weakened tunneling nanotubes (TNTs) and compromised cell–cell adhesion in neonatal rat ventricular fibroblasts, as shown by biomechanical studies using optical tweezers ( Lachaize et al, 2021 ). To date, the topic of lamin mechanics is still vastly unstudied, and this application of optical tweezers could definitely be extended to examine the mechanics of other mutant lamins, as well as any other intermediate filaments.…”
Section: Single-molecule Studies Of Cardiovascular Diseasesmentioning
confidence: 99%
“…Furthermore, cell adhesion plays a key role in health and disease: for example, the impairment of adhesiveness is typical in the pathogenesis of certain diseases, like ACM, where the speculated detachment of cardiomyocytes due to altered cell–cell junctions is thought to trigger the disorder. It has been previously reported by our group that neonal rat ventricula fibroblast (NRVF) carring LMNA D192G mutation present reduced cell–cell adhesion properties when compared with control (non-mutated NRVF [ 50 ]. Adhesive properties and events are usually derived from the retraction segment of a F-d curve.…”
Section: Force Spectroscopy With Afmmentioning
confidence: 99%
“…Veronique Lachaize and coworkers detailed, for this Special Issue, the biophysical and biomechanical impact of the LMNA D192G missense mutation on neonatal rat ventricular fibroblasts (NRVF). They evidenced a decreased elasticity, a disturbed cytoskeleton organization and altered cell-to-cell adhesion properties in the cardiac fibroblasts with LMNA D192G mutation [ 9 ]. As similar observations have been made before in cardiomyocytes with a mutation of LMNA D192G [ 10 ], the recent findings of Lachaize et al clearly indicate the importance of LMNA mutations for ACM, as in addition to cardiomyocytes, cardiac fibroblasts are also highly biomechanically impacted by this mutation [ 9 ].…”
mentioning
confidence: 99%